Relationship Between Mother's Knowledge And Clean And Healthy Living Behaviors Towards Fever Typoid In Toddlers - Sry Rizki; Asmima Yanti; Siti Damayanti (International Journal of Public Health, 2024)
One of the tropical infectious diseases in developing countries is typhoid fever. Typhoid fever is often found in people's lives, both in urban and rural areas. This disease is very closely related toclean and healthy living behavior(PHBS) such as poor environmental sanitation, personal hygiene and daily community behavior. Purpose To find outThe Relationship between Mother's Knowledge and Clean and Healthy Living Behavior towards Typhoid Fever in Toddlers in the Children's Ward of Dr. H. Yulidin Away Tapaktuan Regional Hospital. This research method is descriptive correlation with Cross Sectional approach with a sample size of 52 parents with typhoid fever cases. The results of this study obtained p-value results = 0.000 <0.05 so that there is a relationship between the two variables. Conclusion There is a significant relationship between the level of knowledge with clean and healthy living behavior (PHBS) on typhoid fever in toddlers in the children's room of Dr. H Yulidin Away Tapaktuan Hospital. Suggestions from the results of this study provide input to service institutions and become guidelines for maximizing the implementation of clean and healthy living behavior (PHBS) in parents whose children are being treated with typhoid fever cases.